Developing a Reinforced Portland Cement using Nano Materials for CO2 Sequestrated Reservoirs - Tiong, Michelle (Curtin University, 2019)
Due to the salient features of nanomaterials, Nano glass flakes (NGFs) and multiple-walled carbon nano tubes (MWCNTs) were used to enhance the durability of Class G cement for CO2 sequestrated reservoirs. A series of pre and post carbonation tests were conducted and it was revealed that MWCNTs could give a better performance in terms of cement strength whilst NGFs could be a better solution in terms of resistance against the attack of CO2.